PID control of SMA fibers. Hysteresis consideration, and time extension reduction using electrical resistance measurement - López Fernández, Rafael Francisco; Tomás Balibrea, Luis Manuel; Doménech Asensi, Ginés (Rev. Téc. Fac. Ing. Univ. Zulia)
SMA fibers can be used as mechanical actuators, since like electrical muscles, they modify their length as temperature changes. Metallographic transformation, which causes shape variation, takes place in a narrow temperature margin, requiring a controller that causes mechanical position feedback, in order to adjust the power supply needed to reach desired position. The alloy used has been NiTi, heated by an electrical current, and cooled by natural convection. Two main problems are the strong transformation hysteresis and the great cooling time, because of natural convection. To control the hysteresis, two PID regulators have been used, which are chosen depending on the transformation direction. As to cooling time optimization and relaxation, they have been reduced in certain cases by modifying the point at which transformation moment occurs, using electrical fiber resistance measurement. Finally, after presenting experimental results, a discussion is developed about SMA actuator restrictions.